A brown dwarf donor and an optically thin accretion disc with a complex stream impact region in the period-bouncer candidate BW Sculptoris - Neustroev Vitaly V.; Mäntynen Iikka (OXFORD UNIV PRESS, 2025)
We present an analysis of multi-epoch spectroscopic and photometric observations of the WZ Sge-type dwarf nova BW Scl, a period-bouncer candidate. We detected multiple irradiation-induced emission lines from the donor star allowing the radial velocity variations to be measured with high accuracy. Also, using the absorption lines Mg ii 4481 Å and Ca ii K originated in the photosphere of the accreting white dwarf (WD), we measured the radial velocity semi-amplitude of the WD and its gravitational redshift. We find that the WD has a mass of 0.85 ± 0.04 M⊙, while the donor is a low-mass object with a mass of 0.051 ± 0.006 M⊙, well below the hydrogen-burning limit. Using NIR data, we put an upper limit on the effective temperature of the donor to be ≲1600 K, corresponding to a brown dwarf of T spectral type. The optically thin accretion disc in BW Scl has a very low luminosity ≲4 × 1030 erg s−1 which corresponds to a very low-mass accretion rate of ≲7 × 10−13 M⊙ yr−1. The outer parts of the disc have a low density allowing the stream to flow down to the inner disc regions. The brightest part of the hotspot is located close to the circularization radius of the disc. The hotspot is optically thick and has a complex elongated structure. Based on the measured system parameters, we discuss the evolutionary status of the system.